CHARACTERIZATION AND PROPERTIES INVESTIGATION OF AUTOMOTIVE STEEL EXHAUST PIPING FAILURE - KHAIRDDIN, MUHAMAD FIKRI (IRC, 2017)
Incident involving failures of steel exhaust elbow pipe connected to a muffler of Proton Persona investigated carrying raw gas has caused serious disruption within the system. This study looks at developing useful approaches and strategies to forecast failure of exhaust piping system for automotive applications. Existing design, manufacturing process and exhaust pipe material as well as operating condition have been reviewed and analyzed using Non-Destructive techniques (NDT) and Destructive techniques (DT). Vickers hardness test conducted using 100kgf load on the failed materials indicated the exhaust pipe fulfill the tensile strength requirement based on industry specification to carry out intended function. Metallographic analysis conducted using optical microscope as well as Scanning Electron Microscope (SEM) at various magnifications indicated multiple evidences of internal corrosion and micro-fractures on steel exhaust pipe surface. Besides, computational Fluid Dynamics (CFD) results showed that the elbow of the exhaust pipe have been exposed to an extreme exhaust gas flow gradient. The high risk elbow area exposed to high velocity, pressure and temperature simulated by Computational Fluid Dynamics (CFD) simulation coherence to the leakage area of the exhaust pipe. Root Cause Analysis (RCA) showed that phenomenon excessive thinning of steel pipe wall caused by erosion-corrosion mechanism exhaust pipe lead to the perforation of an exhaust pipe. Based on the data collected, it is suggested, proper process design of the product may be implemented during installation and fabrication of exhaust piping system, followed by revising and improving gas stream flow inside the exhaust pipe system as well as using corrosion inhibitor in order to avoid occurrence of same failure in future.